2021
DOI: 10.1186/s13018-021-02751-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of anti-osteoporosis mechanisms of Rehmanniae Radix Preparata based on network pharmacology and experimental verification

Abstract: Background Rehmanniae Radix Preparata (RRP) can effectively improve the symptoms of osteoporosis, but its molecular mechanism for treating osteoporosis is still unclear. The objective of this study is to investigate the anti-osteoporosis mechanisms of RRP through network pharmacology. Methods The overlapping targets of RRP and osteoporosis were screened out using online platforms. A visual network diagram of PPI was constructed and analyzed by Cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Luteolin belongs to the flavone family commonly present in plants. Studies have shown that both isolated luteolin and plant extracts have anti-inflammatory activity [3839]. Luteolin-7-O-Glucuronide (L7Gn), an active component of luteolin, has been identified to prevent overproduction of inflammatory mediators including IL-6, IL-1β and cyclooxygenase 2 [40].…”
Section: Discussionmentioning
confidence: 99%
“…Luteolin belongs to the flavone family commonly present in plants. Studies have shown that both isolated luteolin and plant extracts have anti-inflammatory activity [3839]. Luteolin-7-O-Glucuronide (L7Gn), an active component of luteolin, has been identified to prevent overproduction of inflammatory mediators including IL-6, IL-1β and cyclooxygenase 2 [40].…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptor 1(ESR1) is the host gene of hsa_circ_0078309, which is an estrogen receptor subtype widely expressed in bone tissue ( 82 ). Studies have illustrated that estrogen plays a role in regulating bone metabolism mainly by interacting with ESR1 ( 83 ). So, has_circRNA_0078309 may regulate bone metabolism of PMOP.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen signaling pathway is essential for the development of OP. Estrogen is an important regulatory hormone in the human body, and its physiological role is mainly to regulate the transcription and translation of target genes by acting on the estrogen receptors of tissue cells 85 . As the major estrogen receptor subtype in bone tissue, ESR1 also plays an important role in regulating bone metabolism.…”
Section: Discussionmentioning
confidence: 99%